OPTIMIZING EXAM SCHEDULES: A LITERATURE SURVEY - Mamay, Kuanyshbek (Journal of Emerging Technologies and Computing, 2023)
Exam scheduling is a challenging problem that involves finding anoptimal schedule for a set of exams subject to various constraints, such as roomcapacities, time windows, and conflicting exams. This problem has beenextensively studied in operations research and computer science and variousmethods have been proposed over the years. In this paper, we present acomprehensive literature review of the existing methods for exam schedulingoptimization. We summarize the key contributions, strengths, and weaknessesof each approach and compare and contrast the various methods based on variousperformance measures such as solution quality, computational time, andscalability. Additionally, we discuss the real-world applications of the examscheduling problem and the impact of different methods on practical solutions.Finally, we provide insights into the current state of the art in exam schedulingand suggest future directions for research. Our survey provides a useful resourcefor researchers, practitioners, and decision-makers who are interested in examscheduling optimization.